Interview with Maria Giovanna Arcamone: a journey through Onomastics and Toponomastics - Arcamone, Maria Giovanna; Carvalhinhos, Patricia; Giuntoli, Giacomo (Linha D'Água, 2023)
Prof. Arcamone's contributions to the studies of onomastics and toponymy in over half a century of incessant work are truly invaluable. One only needs to consider her pioneering work on Lombard toponyms or her decisive contribution to the Italian literary onomastic scene through the founding of il Nome nel testo with the late Professor Davide De Camilli and Professor Donatella Bremer. But this is obviously an infinitesimal drop of an important author that has been able to inspire generations of scholars not only through her essays and books but also with a never-ending reflection on research methodology. This interview allows us to revisit some of the stages of the key moments of Professor Arcamone's extraordinary lifelong research. Through her work, she has demonstrated that the study of names is not simply an inert academic subject, but rather a way to better and deeply understand the complex world in which we live.